PENERAPAN METODE KARYAWISATA BAGI PEMBELAJARAN ANAK USIA DINI - Sjeny Liza Souisa (TANGKOLEH PUTAI, 2018)
This paper describes the application of field trips for early childhood learning. One of the most important elements in education includes PAUD is an educator or teacher who has professional competence, pedagogical competence, personality competence and social competence. In Undang-undang Nomor 14 tahun 2005 concerning Teachers and lecturers it is stated that teachers are professional educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in early childhood education in formal education, basic education, and secondary education. In conjunction with teaching and learning activities, the notion of tourism is that students will learn an object where the object is located. Thus, what is called work actually is meant to learn something. Tourism is a method of pursuit carried out by inviting students to visit an event or place that has something to do with something discussed. The method of tourism is a way of presenting learning material by bringing students directly to the object being studied, and the object is outside the class. Thus, what is called work actually is meant to learn something.